2023
DOI: 10.2478/rjim-2022-0018
|View full text |Cite
|
Sign up to set email alerts
|

A review of transthyretin cardiac amyloidosis

Abstract: Transthyretin cardiac amyloidosis is a progressive disease known to cause heart failure, conduction anomalies, and arrythmias. Due to poor outcomes and mortality from severe cardiomyopathy, prevalence and incident rates are often underreported. As global longevity is increasing and rates of amyloidosis are also increasing, there is a need to improve diagnostic and therapeutic interventions. Previously, symptom management and transplantation were the mainstay of treatment for heart failure symptoms, but studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A review of the literature showed that carpal tunnel syndrome is a common early clinical feature of cardiac TTR amyloidosis, but few reports describe synovitis and elevated CRP associated with TTR amyloidosis [4,6,7]. The finding of moderate synovitis with moderate Doppler signal in the wrist, which is strongly associated with active inflammatory disease, is an uncommon feature of cardiac TTR amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature showed that carpal tunnel syndrome is a common early clinical feature of cardiac TTR amyloidosis, but few reports describe synovitis and elevated CRP associated with TTR amyloidosis [4,6,7]. The finding of moderate synovitis with moderate Doppler signal in the wrist, which is strongly associated with active inflammatory disease, is an uncommon feature of cardiac TTR amyloidosis.…”
Section: Discussionmentioning
confidence: 99%